PENERAPAN SANKSI PELANGGARAN DISIPLIN PEGAWAI NEGERI SIPIL BERDASARKAN PERATURAN PEMERINTAH NOMOR 94 TAHUN 2021 (STUDI DIKABUPATEN MELAWI) - NIM. A1012221188, SYAMSURI (Fakultas Hukum Universitas Tanjungpura, 2026)
Abstract Government Regulation (PP) Number 94 of 2021 concerning Civil Servant Discipline is principally intended to improve discipline and create a professional, dedicated, and integrity-based Civil Servant apparatus, thereby supporting good governance.The Melawi Regency Governmentisoneoftheregenciesin Wes tKalimantan Province with a significant number of Civil Servants. Between 2022 and 2025, several cases related to civil servant disciplinary violations were reported. Although the regulation shavebeenim plemented,sanction sarestillbeingimposedthatdonotcomply with Government Regulation Number 94 of 2021. Therefore, to determine whether the implementation of disciplinary sanctions for civil servant violations in Melawi Regency is in accordance with Government Regulation Number 94 of 2021 and what the causes orobstaclesare ,theauthorconductedastudyentitled